Effect of Family Climate, Mental Health on Students‟ Academic Achievement: An Empirical Study - Maitri,; Singh, Samarth (International Journal of Psychosocial Rehabilitation, 2020)
Family is the basic entity of existence for an individual. It forms the foundation during the formative stage of life, which imprints life along with us. The mental health of an individual gets determined by its overall surroundings; family is one of the biggest predictors of the status of mental health. Both family climate and mental health have a direct bearing on students’ academic achievement. All parents and teachers are concerned about students’ academic performance. In the present study, 200 class XII (science stream) students in Delhi are studied to examine the effect of students’ family climate, i.e., independence and healthy climate, along with students’ mental health—emotional stability and intelligence—on their achievement in XII exams. The results confirmed a significant contribution of both variables to students’ performance.